Islamic Counseling on Psychological Aspects of the Sirri Marriage Case: Five Women’s Voices in the Narrative Investigation - Nuraeni, Heni Ani; Astuti, Sri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
Unregistered marriages have become a phenomenon in several countries and have an impact on wives and children because marriages are not registered with the government. This research aims to report the psychological impact on wives and children in Indonesia. Five female participants in unregistered marriages were involved in narrative inquiry research. Data collection was carried out through semi-structured interviews. Interviews were also conducted with ustadz and amil (community figures). The data were analyzed using narrative analysis. The results showed that the wives experienced mental disorders (neuroses), which were influenced by frustration (pressure), conflict (inner conflict) and anxiety due to several things, including the lack of legal certainty and treatment of the husband. Apart from that, the factors causing unregistered marriages are women’s ignorance of the concept of marriage, which includes the rights and obligations of husband and wife, and economic aspects. This research has implications for the legality of children resulting from unregistered marriages related to inheritance and administration rights.